Effect of aging on the cerebral metabolic mechanism of electroacupuncture treatment in rats with traumatic brain injury - Huo, Bei-Bei; Zheng, Mou-Xiong; Hua, Xu-Yun; Wu, Jia-Jia; Xing, Xiang-Xin; Ma, Jie; Fang, Min; Xu, Jian-Guang (Frontiers in Neuroscience, 2023)
Objective Aging has great influence on the clinical treatment effect of cerebrovascular diseases, and evidence suggests that the effect may be associated with age-related brain plasticity. Electroacupuncture is an effective alternative treatment for traumatic brain injury (TBI). In the present study, we aimed to explore the effect of aging on the cerebral metabolic mechanism of electroacupuncture to provide new evidence for developing age-specific rehabilitation strategies. Methods Both aged (18 months) and young (8 weeks) rats with TBI were analyzed. Thirty-two aged rats were randomly divided into four groups: aged model, aged electroacupuncture, aged sham electroacupuncture, and aged control group. Similarly, 32 young rats were also divided into four groups: young model, young electroacupuncture, young sham electroacupuncture, and young control group. Electroacupuncture was applied to “Bai hui” (GV20) and “Qu chi” (LI11) for 8 weeks. CatWalk gait analysis was then performed at 3 days pre- and post-TBI, and at 1, 2, 4, and 8 weeks after intervention to observe motor function recovery. Positron emission computed tomography (PET/CT) was performed at 3 days pre- and post-TBI, and at 2, 4, and 8 weeks after intervention to detect cerebral metabolism. Results Gait analysis showed that electroacupuncture improved the forepaw mean intensity in aged rats after 8 weeks of intervention, but after 4 weeks of intervention in young rats. PET/CT revealed increased metabolism in the left (the injured ipsilateral hemisphere) sensorimotor brain areas of aged rats during the electroacupuncture intervention, and increased metabolism in the right (contralateral to injury hemisphere) sensorimotor brain areas of young rats. Results This study demonstrated that aged rats required a longer electroacupuncture intervention duration to improve motor function than that of young rats. The influence of aging on the cerebral metabolism of electroacupuncture treatment was mainly focused on a particular hemisphere.